Hogar SOS - Aguilar Velazco, Liz Margot (2023)
The main objective of the Master's Thesis "Hogar SOS" is to evaluate the viability of a business model through a digital platform for domestic emergency care in Lima, Peru. Having achieved the feasibility objectives of the business model, we are sure that we will be able to take the next steps of both regional and global scalability. The study was carried out through two research methods: a survey aimed at potential users and a series of interviews with experts in the field of domestic emergency services. The survey results revealed that the majority of potential users were willing to use an app to connect with specialists in the event of a home emergency, and that they valued the speed, quality of service, guarantee, payment flexibility, and security in the app. On the other hand, the experts interviewed revealed that the domestic emergency services market is highly competitive and that customer service, service quality and speed of response are key factors for success in this market. Based on the results obtained, a business model based on a digital platform that connects users with specialists in domestic emergency services is proposed. The platform would be responsible for intermediation between users and specialists, guaranteeing speed, quality of service, security and flexibility of payment. The business model will start with financing from the company's partners until it is self-sustaining from its own income from the commission that will be charged to both users and technical specialists for each request. The initial investment is expected to be recovered from the second year of operation, by exceeding the cost of shareholders' capital (COK) of 23.8%. For the project, a financial net present value (VAN) of S/. 360,996 and a TIR of 100.36% for a projection during the first 5 years of operation. The initial success of the platform will focus on the attention of specialized technicians according to availability and coverage in some districts of Lima Metropolitana. It is planned to start with a white march in the district of Santiago de Surco and progressively extend operations throughout the city. Based on the results of these operations, it is intended to expand the services at the regional level.